Comparison of flexural design between bs 8110 (1985) and aci 318 (1995) - Loo, Soon Wah (Universiti Malaysia Sarawak (UNIMAS), 2000)
This study compares the flexural design for arbitrary rectangular sections of reinforced concrete beams between BS 8110 (1985) and ACI 318 (1995). The main objectives of this study are to identify a more conservative design approach and to obtain a set of design aids such as charts and tables for ACI 318 (1995). This study includes the different analysis and design procedures of both codes and the interpretation of effects in flexural design.